REPORT ON CULTURAL FIELD RESEARCH IN MANGOCHI DISTRICT, MALAWI, July 15 to August 25, 1983 - Kubik, Gerhard (International Library of African Music, 1983)
Our current six-month research project on “Systems of traditional education in East andCentral Africa” which we are carrying out in affiliation with the Centre for Social Research, University of Malawi, Zomba, (Director: Louis A.H. Msukwa) and with financial assistance from the Foundation for the Advancement of Scientific Research, Vienna (Project No. 4977) has had a very good start in Malawi and we have just completed a fruitful first period of field studies in Mangochi District.
Keywords: African Music; Malawi; Field Research